Porphyrin biosynthesis. VII. Porphyrinogen carboxy-lyase from avian erythrocytes. Purification and properties - Tomio, J.M. (1970)
1. 1. Uroporphyrinogen carboxy-lyase (EC 4.1.1.d), the enzyme catalysing the decaroxylation of uroporphyrinogen to coproporphyrinogen, has been isolated from normal chicken erythrocytes. The enzyme was purified 220-fold with a yield of 24% from haemolysate supernatant by DEAE-cellulose batch treatment, (NH4)2SO4 fractionation and chromatography on DEAE-cellulose. 2. 2. The purified material appears to be homogeneous in polyacrylamide gel disc electrophoresis. 3. 3. The enzyme was heat labile and inhibited by sodium salt; the activity was enhanced by EDTA, GSH and boiled rat-liver extract. 4. 4. The influence of these chemical and physical agents on the removal of the first and second carboxyl groups from uroporphyrinogen was compared; the second group was more susceptible to these agents. 5. 5. The possibility that one or several enzymes were involved in the stepwise decarboxylation of uroporphyrinogen is discussed. 6. 6. The general name of porphyrinogen carboxy-lyase for the enzyme system is proposed because of the different porphyrinogens it can decarboxylate. © 1970.